Engaging Transgender People in NIH-Funded HIV/AIDS Clinical Trials Research. (15th August 2016) - Siskind, Rona L.; Andrasik, Michele; Karuna, Shelly T.; Broder, Gail B.; Collins, Clare; Liu, Albert; Lucas, Jonathan Paul; Harper, Gary W.; Renzullo, Philip O.
Abstract : Abstract: In 2009, the National Institutes of Health recognized the need to expand knowledge of lesbian, gay, bisexual, and transgender (LGBT) health and commissioned the Institute of Medicine to report on the health of these populations in the United States. The resulting Institute of Medicine publication called for more knowledge of the health of LGBT populations, as well as improved methodologies to reach them, more LGBT-focused research, and enhanced training programs and cultural competency of physicians and researchers. Several of the National Institutes of Health–funded HIV/AIDS clinical trials networks, including the Adolescent Medicine Trials Network for HIV/AIDS Interventions, HIV Prevention Trials Network, HIV Vaccine Trials Network, and Microbicide Trials Network, have focused attention on engaging transgender (TG) individuals in research. They have identified issues that transcend the nature of research (ie, treatment or prevention, adult or adolescent) and have adopted various approaches to effectively engage the TG community. Each network has recognized the importance of developing partnerships to build trust with and seek input from TG individuals on research plans and policies. They have established standing advisory groups and convened consultations for this purpose. To ensure that trial data are reflective of the participants they are seeking to enroll, they have reviewed and revised data collection forms to incorporate the 2-step method of collecting sex at birth and gender identity as 2 independent variables, and some have also revised research protocol templates and policies for concept development to ensure that they are appropriate for the inclusion of TG participants. The networks have also initiated trainings to enhance cultural sensitivity and developed a range of materials and resources for network and clinical research site staff. They continue to identify TG-specific research needs in an effort to be more responsive to and improve the health of TG individuals, particularly related to HIV/AIDS.